Impacts of truck platooning on the multimodal freight transport market: An exploratory assessment on a case study in Italy. (September 2022) - Marzano, Vittorio; Tinessa, Fiore; Fiori, Chiara; Tocchi, Daniela; Papola, Andrea; Aponte, Dario; Cascetta, Ennio; Simonelli, Fulvio
Highlights: Exploratory analysis of system-wide competition between existing freight modes and truck platooning. Cost of various freight modes compared, leveraging a multimodal nationwide freight supply model. Forty different scenarios modelled, with different assumptions on the input variables including three levels of automation. Truck platooning could be convenient in medium to large distances, with competition mainly with traditional road and rail freight transport. It would be appropriate to consider track platooning as a new freight transport mode. Abstract: Truck platooning is expected to significantly affect road freight transport performances, although in the long term due to technological and operational issues still to address. Furthermore, truck platooning could be introduced with increasing levels of automation, corresponding to different technologies and operational costs. In parallel, various Countries promote freight-related infrastructural plans pursuing a modal shift from the road towards more sustainable modes (railways, sea shipping, inland waterways). The planning horizon of such infrastructures probably overlaps, at least partially, with a non-negligible market penetration of truck platooning. In this framework, the paper aims to explore the extent of a system-wide competition between existing freight modes and truck platooning, through an exploratory analysis of the potential market of truck platooning in Italy. The study is based on a comparative analysis of the cost of various freight modes, leveraging a multimodal nationwide freight supply model. Forty different scenarios have been modelled, with different assumptions on the input variables including three levels of automation. Results show that truck platooning could be highly competitive with respect to rail transport for medium to large distances. Competition with conventional road transport is significant as well, with a large contestable market share between truck platooning and traditional road freight, especially on medium to long distances, whilst maritime transport starts competing with truck platooning only in the case of (at least partially) unmanned truck platooning operations. The size of truck platoons impacts appreciably on results only with a manned leader truck and unmanned followers. Based on the above results it would be appropriate to consider track platooning as a new freight transport mode.